An Atypical Shallow Mw 5.3, 2021 Earthquake in the Western Corinth Rift (Greece). Issue 9 (18th September 2022) - Zahradník, Jiří; Aissaoui, El Madani; Bernard, Pascal; Briole, Pierre; Bufféral, Simon; De Barros, Louis; Deschamps, Anne; Elias, Panagiotis; Evangelidis, Christos P.; Fountoulakis, Ioannis; Gallovič, František; Kapetanidis, Vasilis; et al.
Abstract: Moderate‐to‐large earthquakes in rifts may occur on leading boundary faults or inner antithetic faults. Here we show a rare case of the 2020–2021 seismic sequence in the Corinth rift, that culminated in the shallow rupture of the antithetic fault, neither preceded nor followed by the leading fault rupture. The hypocenter of the largest shock (Mw 5.3 of 17 February 2021) was located at ∼8 km depth. However, seismic waveform data, supported by satellite‐geodetic and tide gauge measurements, pointed to rupture at shallow depth (∼3 km), where no earthquakes were previously observed. We show that the earthquake most probably ruptured two orthogonal, conjugate fault segments: a weak nucleation phase occurred in the microseismically highly active sub‐horizontal detachment layer, followed – a few seconds later – by a larger, shallow moment release on a high‐angle, south‐dipping normal fault. The latter is the Mornos offshore fault, antithetic to the leading, north‐dipping Psathopyrgos fault. Our study presents the first instrumental/observational evidence of a very shallow Mw 5+ event in this rift – and one of the few reported worldwide. The depth limit of the main shallow slip patch coincides with the expected crossing of the Mornos fault with the Psathopyrgos fault, stressing the importance of fault segmentation and rooting inherited from the rift history. This unusual shallow slip in a depth range with little background seismicity and few aftershocks needs to be further investigated by dynamic modeling as a possible prototype of hazardous events in rift environments. Plain Language Summary: The Corinth rift is a key tectonic element in the Eastern Mediterranean, separating mainland Greece from the Peloponnese. The rift is highly seismically active, yet geologically complex and not fully understood. Between December 2020 and February 2021, thousands of small earthquakes and two Mw > 5 events occurred there. Microearthquakes migrated in the rift on a subhorizontal detachment layer, separating the brittle and ductile crust. Similar activity has been well known for decades. However, the Mw 5.3 mainshock of February 17 was peculiar. While it nucleated at a depth of ∼8 km on the detachment, most of the slip occurred at unusually shallow depths of ∼0–5 km. This major rupture segment, well constrained by seismic, geodetic, and tide gauge data, is interpreted here as a rare shallow activation of a south‐dipping offshore western continuation of the Trizonia fault system. This continuation is most likely the Mornos fault, lying opposite (antithetic) to the major north‐dipping Psathopyrgos fault which outcrops on the southern coast. The present complexity of these structures is a result of the tectonic evolution of the rift during the last 0.4 Myr. The gained knowledge, supplemented by new offshore measurement techniques, will improve seismic and tsunami hazard assessment. Key Points: Seismic, geodetic and tide gauge records in Corinth rift reveal a rare shallow rupture (∼0–5 km) on a south‐dipping offshore normal fault The shallow rupture was preceded, triggered, and followed by microearthquakes mostly occurring deeper, on the detachment layer The causative fault is along‐dip segmented and rooted beneath detachment as inherited from fault interactions during the rift evolution